NONSPECIFIC REACTIVE HEPATITIS AT PATIENTS WITH GALLSTONE DISEASE - Bychkov, S.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
In work it is conducted patomorphological research of liver structure at patients with cholecystolithiasis. It is shown as a result of the conducted patomorphological researches, that at patients with cholecystolithiasis takes place reactive hepatitis, which necessitates conducting of correcting medicinal therapy in preoperative and postoperative periods.